Educating students on the autistic spectrum : a practical guide - Hanbury, Martin. 4 0 16; 5 (Los Angeles : Sage Publications, 2012)
Presents a guide on how to educate autistic students, focusing on the impact of autism on learning, sharing positive attitudes towards students with autism, addressing behavioral issues in autism, and other topics.
Previous ed. titled: Educating pupils with autistic spectrum disorder.
Includes bibliographical references (p. [122]-125) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Education;Education. -- Autistic children;Autistic children -- Great Britain; 20; 2